SISTEM EKONOMI ISLAM MENURUT PARA AHLI - Nuruddin Armanto (Faculty of Islamic Economics and Business, 2021)
Islamic economy is essentially a part of the interaction system in an effort to allocate resources with the aim of welfare and improving the standard of human life which is of course based on Islamic values ​​in it. The emergence of history related to economics in Islam does not need to start from a discussion about economics that is connected with the Al-Quran and Sunnah. But basically the views regarding economic issues relate to the companions of the Prophet and the generation who followed them. Not a few of them are part of legal experts who come from Eminence. What are the opinions or thoughts of historians about Islamic economics in which they discuss every concept of economic history of Ibn Hazm, Nizam al Mulk and Al Syatibi?